Advanced electron tomography of nanoparticle assemblies(a)Contribution to the Focus Issue Self-assemblies of Inorganic and Organic Nanomaterials edited by Marie-Paule Pileni. (10th October 2017) - Altantzis, T.; Zanaga, D.; Bals, S.
Abstract: Nanoparticle assemblies have attracted enormous scientific interest during the last years, due to their unique properties compared to those of their building blocks. To understand the origin of these properties and to establish the connection with their structure, a detailed and quantitative structural characterization is essential. Transmission electron microscopy has been widely used to investigate nano-assemblies. However, TEM images only correspond to a two-dimensional projection of a three-dimensional object. Therefore, in order to obtain the necessary 3D structural information electron tomography has to be applied. By means of advanced electron tomography, both qualitative and quantitative information can be obtained, which can be used for detailed theoretical studies.